An Online-based Application of Health Education Media for Prolanis Participants - Wijayanta, Setya; Naryanti, Indah (Procedia of Engineering and Life Science, 2024)
Prolanis is a government program to reduce the prevalence of chronic diseases and prevent patients with chronic diseases from entering the complication stage. In Prolanis activities conducted by health facilities or Fasyankes, Prolanis participants sometimes come late to the health education activities, so participants do not receive information or benefit from health education activities. The purpose of this study is to investigate the use of online-based health education media for Prolanis participants. This research method is descriptive, with primary data sources from the interviews, documentation studies and literature. The application is developed using the prototype method. The Prototypes is created, evaluated, and continued to the implementation stage. The result of this research shows the developing of an online-based application for presenting health education materials to Prolanis participants. This application was tested on Prolanis participants from Padangsari Puskesamas in Semarang City and received positive responses from them. However, some participants still complained about the limited access to smartphones and the assistance need for elderly participants.